Parental Evaluation of Botulinum Toxin Therapy in Children with Cerebral Palsy: A Cross‑Sectional Study from Western Libya and Its Clinical Implications - Fayrouz Abu Alasad; Einass Ragab; Wafa Alshaiby (AlQalam Journal of Medical and Applied Sciences, 2026)
Cerebral palsy (CP) is a common childhood motor disorder caused by non-progressive brain injury or malformation during early development, leading to muscle spasticity and coordination problems. This cross-sectional study aims to evaluate parental satisfaction with botulinum toxin type A BoNT-A) treatment in children with cerebral palsy, focusing on perceived effectiveness and side effects. The study’s objectives include collecting demographic and clinical information, assessing parental knowledge of BoNT-A, evaluating treatment outcomes, monitoring side effects, and measuring overall patient satisfaction. The study involved 75 children aged 1 to 5 years, mostly affected by birth-related oxygen deprivation. Data collected from parents showed significant improvements in muscle tone and daily activities following BoNT-A treatment, with most parents expressing positive satisfaction despite some mild side effects. The findings suggest that BoNT-A is a safe and helpful treatment when combined with rehabilitation therapies. This study highlights the importance of educating parents about BoNT-A treatment and emphasizes the need for careful patient selection and follow-up to achieve optimal results. Increasing awareness among healthcare providers and families can improve treatment experiences for children with cerebral palsy.